Manutenção e reparo de rodovias: estudo de caso de trecho da BR 427 - Nascimento, João Paulo Silva do (Universidade Federal Rural do Semi-Árido, 2018)
The construction of roads arose from the moment in which the man had to travel by greater routes in less time, and has been improving in function of science and technology. With the growth of urban traffic, the construction of these works required a large investment in infrastructure to provide good trafficability with comfort and safety to users. However, currently with all the technological equipment available, many Brazilian highways are still in a state of deterioration, showing us that it is not enough just to build more highways, the maintenance of the pavement must be performed indispensably. The objective of this work is to evaluate the operation of the Buraco BEC (Construction Engineering Battalion) in BR 427, located between the municipalities of Jardim do Seridó / RN and Acarí / RN. step by step of the services performed in the operation. The work was developed from the on-site visits to the BR-427 in May 2018, with the visit it was possible to make a visual observation of the pathological manifestations, photographic records and application of a questionnaire Based on the Standard of the DER / PR ES- P 12/05, this standard prescribes the step by step on the completion of the hole cover operation. At the end of this evaluation, it was verified the occurrence of several defects, such as: cracks, sinkings, wear and pans, these were being recovered with the advance of the services of the lid hole operation. Thus, with the analysis carried out along the route, it was possible to conclude that the pavement was not providing conditions of comfort and safety to its users, due to the high degree of deterioration of its surface which was being minimized with the accomplishment of the maintenance performed by the 1st BEC, the services were performed according to what was specified in the DER / PR ES-P 12/05 standard following all steps of cutting, cleaning the region, applying the emulsion, discharging the PMF and finally compaction. However, the service life of the floor should be extended, increasing the maintenance interval.
Monografia
Keywords: BR 427; Manifestações patológicas; Operação tapa buraco; BR 427; Pathological manifestations; Operation cover hole; ENGENHARIAS::ENGENHARIA CIVIL